DREAMS AND REALITY OF THE ACADEMICIAN I.G. KALINENKO IN CREATION OF DURUM WINTER WHEAT - N. E. Samofalova (Зерновое хозяйство России, 2018)
The article gives the analysis of 40-years selection activity of the academician I.G. Kalinenko in creation of the own initial material and the varieties of turgid and durum wheat which was new for the conditions of the Rostov region. The author gives characteristics of the initial material and the varieties on productivity, adaptability and other economic-valuable traits and properties in different period of I.G. Kalinenko work. His methods of work, initial material, a number of cycles of hybridization while creation of the varieties ‘Novinka’, ‘Novinka 2’, ‘Novinka 3’, ‘Novinka 4’, ‘Donskoy Yantar’ and other have been shown in the article. The author determines the principle role of step (gradual) hybridization to combine the desired traits and properties in the single genotype with the use of the varieties and intermediate forms of own selection, obtained in the creation of such varieties as ‘Aksinit’, ‘Kurant’, ‘Agat Donskoy’, ‘lazurit’, ‘Kristella’, ‘Oniks’. Their potential productivity is 8-10 t/ha, as the productivity of the best varieties of soft winter wheat, which the scientist, talented researcher, academician I.G. Kalinenko hoped to receive, starting breeding of durum winter wheat in 1961.